1996
DOI: 10.1136/thx.51.2.169
|View full text |Cite
|
Sign up to set email alerts
|

Asthma, airways responsiveness and air pollution in two contrasting districts of northern England.

Abstract: Background -To assess the possible magnitude of differences between normal populations an epidemiological investigation ofasthma was conducted in two strongly contrasting districts of northern England -rural West Cumbria on the west coast and urban Newcastle upon Tyne on the east coast. Methods -A cross sectional survey of randomly identified men aged 20-44 years was conducted in two phases: phase 1, a postal survey of respiratory symptoms and asthma medication in 3000 men from each district; and phase 2, a cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…Estimates of the proportion of 'ghosts' among non-responders have varied considerably and were up to 25% in studies in North East England. 9,14,15 Were there to have been an actual rise in the prevalence of ghost patients, our results would in fact underestimate the decline in survey response rates. Sender recognition may be a further factor affecting response.…”
Section: T I O N P R O H I B I T E Dmentioning
confidence: 60%
“…Estimates of the proportion of 'ghosts' among non-responders have varied considerably and were up to 25% in studies in North East England. 9,14,15 Were there to have been an actual rise in the prevalence of ghost patients, our results would in fact underestimate the decline in survey response rates. Sender recognition may be a further factor affecting response.…”
Section: T I O N P R O H I B I T E Dmentioning
confidence: 60%
“…Using this methodology, PD20 values v200 mg are usually associated with active asthma, values 200-1,000 mg are sometimes associated with active asthma, and values w1,000 mg are seldom associated with active asthma [12,15]. The precision of the method is described fully elsewhere [13].…”
Section: Methodsmentioning
confidence: 99%
“…The aim was to recruit 600 subjects for these laboratory studies of each survey. The methods were the same in the two surveys and have been published in detail elsewhere [12,13]. All laboratory studies took place between October and April to avoid the pollen season.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, in adults, community-based studies have found an association between air pollution and bronchitis, but not asthma. [8][9][10][11][12][13] Associations observed between admissions to hospital for respiratory illness and air pollution [14][15][16][17] provide additional evidence for the impact of air pollution on respiratory health. Furthermore, exacerbation of asthma symptoms has been observed among asthmatics exposed to sulphur dioxide (SO 2 ) [18][19][20] and effects are seen at much lower levels than in non-asthmatic subjects.…”
Section: Discussionmentioning
confidence: 99%